Recurrent Instability and Surgery Are Common After Nonoperative Treatment of Posterior Glenohumeral Instability in NCAA Division I FBS Football Players - Tennent, David J. (Clin Orthop Relat Res, 2021)
BACKGROUND: In-season return to play after anterior glenohumeral instability is associated with high rates of recurrent instability and the need for surgical stabilization. We are not aware of previous studies that have investigated in-season return to play after posterior glenohumeral instability; furthermore, as posterior shoulder instability in collision athletes occurs frequently, understanding the expected outcome of in-season athletes may improve the ability of physicians to provide athletes with a better understanding of the expected outcome of their injury and their ability to return to sport. QUESTIONS/PURPOSES: (1) What proportion of athletes returned to play during the season after posterior instability in collegiate football players? (2) How much time did athletes lose to injury, what proportion of athletes opted to undergo surgery, and what proportion of athletes experienced recurrent instability after a posterior instability episode during a collegiate football season? METHODS: A multicenter, prospective, observational study of National Collegiate Athletic Association (NCAA) Division 1 Football Bowl Subdivision athletes was performed at three US Military Service Academies. Ten athletes who sustained a posterior instability event during the regular football season and who pursued a course of nonoperative treatment were identified and prospectively observed through the subsequent season. All athletes in the observed cohort attempted an initial course of nonoperative treatment during the season. All athletes sustained subluxation events initially identified through history and physical examination at the time of injury. None of the athletes sustained a dislocation event requiring a manual reduction. Intraarticular pathology consisting of posterior labral pathology was further subsequently identified in all subjects via MRI arthrogram. Return to play was the primary outcome of interest. Time lost to injury, surgical intervention, and subsequent instability were secondary outcomes. RESULTS: Of the 10 athletes who opted for a trial of initial nonoperative management, seven athletes were able to return to play during the same season. Although these seven athletes returned within 1 week of their injury (median of 1 day), 5 of 7 athletes sustained recurrent subluxation events with a median (range) of four subluxation events per athlete (0 to 8) during the remainder of the season. Seven athletes were treated surgically after the completion of their season, four of whom returned to football. CONCLUSION: This study suggests that although collegiate football players are able to return to in-season sport after a posterior glenohumeral instability event, they will likely sustain multiple recurrent instability events and undergo surgery after the season is completed. The results of this study can help guide in-season management of posterior shoulder instability by allowing more appropriate postinjury counseling and decision making through the identification of those athletes who may require additional attention from medical staff during the season and possible modifications to training regimens to minimize long-term disability. Further prospective studies involving a larger cohort over several seasons should be performed through collaborative studies across the NCAA that better assess function and injury risk factors before beginning collegiate athletics. This would better characterize the natural history and associated functional limitations that athletes may encounter during their collegiate careers. LEVEL OF EVIDENCE: Level IV, prognostic study.